Contextualising coastal management and adaptation: Examining situated practices and path dependencies in Ireland and Germany. (1st April 2022) - Tubridy, Fiadh; Walsh, Cormac; Lennon, Mick; Scott, Mark
Abstract: In the context of climate change, coastal areas around the world face multiple interrelated challenges. A range of 'international best practice' approaches have been proposed to address these, including concepts such as integrated coastal zone management, ecosystem-based management and managed retreat. However, such supposedly mobile and transferable approaches often fail to properly account for the differences between local contexts, leading to implementation failures. In response, this paper mobilises the conceptual lenses of 'situated practices' and 'path dependencies' to demonstrate how the emergence and evolution of approaches to planning in coastal communities can generate policy trajectories that constrain the latitude for alternative options. The paper explores the trajectories of coastal planning on the island of Sylt in Germany and Castlemaine Harbour in Ireland. It identifies important path dependencies associated with institutional inertia, collective memories of past hazards and management strategies, the legacies of previous coastal management measures and of coastal development, and the importance of property relations. Overall, the analysis highlights the importance of appreciating the local and historical distinctiveness of coastal areas and communities. It shows that critical attention to context and creating inclusive fora for debate is required to advance climate change adaptation measures that offer opportunities to unlock historically anchored path dependencies which hamper flexibility and reduce resilience.